2015
DOI: 10.1186/s12938-015-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simvastatin treatment on endothelial cell response to shear stress and tumor necrosis factor alpha stimulation

Abstract: BackgroundStatin drugs are one of the most commonly prescribed pharmaceuticals by physicians. By blocking the rate-limiting step in the cholesterol biosynthesis pathway, statins inhibit cholesterol synthesis, which benefits patient health. However, since many other important cellular processes are regulated within this pathway, they may also be influenced by statin therapy. These pleiotropic effects of statins have not been fully investigated, but are believed to positively influence endothelial cells (ECs), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…It had also been reported that generation of vascular growth factors, conservation of blood vessels and migration of endothelial cells were being improved in the presence of modulating wall shear stress [ 30 , 31 ]. Shear stress derived from flow structures were also found to influence interconnected points between the cytoskeleton and extracellular structures of endothelial cells [ 32 , 33 , 34 ]. However, it was found that elasticity of the vessel wall promotes migratory phenomena of endothelial cells in the presence of lateral stress in the periodic form of lymphatics.…”
Section: Introductionmentioning
confidence: 99%
“…It had also been reported that generation of vascular growth factors, conservation of blood vessels and migration of endothelial cells were being improved in the presence of modulating wall shear stress [ 30 , 31 ]. Shear stress derived from flow structures were also found to influence interconnected points between the cytoskeleton and extracellular structures of endothelial cells [ 32 , 33 , 34 ]. However, it was found that elasticity of the vessel wall promotes migratory phenomena of endothelial cells in the presence of lateral stress in the periodic form of lymphatics.…”
Section: Introductionmentioning
confidence: 99%